Blastocystis and Schistosomiasis Coinfection in a Patient with Chronic Kidney Disease - Colin R. Young; Fred E. Yeo (Case Reports in Medicine)
Chronic kidney disease (CKD) and end-stage renal disease (ESRD) represent a spectrum of impaired immunity with effects on cellular immunity, soluble immune factors, and inflammation. As a result, infections due to impaired immune system responses are responsible for significant morbidity in patients with kidney disease. Because of immune dysfunction in CKD, these patients have reduced probability to clear infections and are susceptible to pathogenic effects of common organisms. We present a case of a patient with CKD coinfected with Schistosoma mansoni and Blastocystis spp. This appears to be the first reported association of Schistosoma mansoni and Blastocystis spp. in a patient with CKD.